Advantages and risks of using steel slag in preparing composts from raw organic waste. Issue 1 (2nd January 2017) - Tu, Xuefei; Aneksampant, Apichaya; Kobayashi, Shizusa; Tanaka, Atsushi; Nishimoto, Ryo; Fukushima, Masami
ABSTRACT: It had been reported that iron and manganese oxides in steel slag enhanced the production of humic acid (HA) from low-molecular-weight compounds, such as phenolic acids, amino acids, and saccharides. In the present study, this function of steel slag was applied to the composting of raw organic wastes (ROWs). The degree of humification of HAs is an important factor in evaluating compost quality. Thus, HAs were extracted from the prepared composts and the humification parameters were determined, in terms of elemental compositions, acidic functional group contents, molecular weights, spectroscopic parameters from UV–vis absorption and 13 C NMR spectra. The timing for adding steel slag affected the degree of humification of HAs in the composts. The weight average molecular weight of a HA when slag was added initially (29 kDa) was significantly higher than when slag was added after elevating the temperature of the compost pile (17–18 kDa). These results show that ROWs are decomposed to low-molecular-weight compounds after the pile temperature is elevated and the presence of slag enhances the polycondensation of these compounds to produce HAs with a higher degree of humification. Because the slag used in the present study contained several-tens ng g −1 to several μg g −1 of toxic elements (B, Cu, Cr, and Zn), leaching tests for these elements from the prepared composts were carried out. Levels for leaching boron from composts prepared by adding slag (0.2–0.4 mg L −1 ) were obviously higher than the corresponding levels without slag (0.05 mg L −1 ).